Polarizer with phase difference layer and image display device with polarizer with phase difference layer
Patent Information
- Application Number
- JP2023126535
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-02
- Publication Date
- 2025-02-14
AI Technical Summary
【0006】 本発明の実施形態によれば、打痕の発生が抑制された位相差層付偏光板を提供し得る。
Smart Images

Figure 2025022188000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizing plate with a retardation layer and an image display device having the polarizing plate with a retardation layer. [Background technology]
[0002] Image display devices, such as liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices, inorganic EL display devices), are rapidly becoming popular. In these image display devices, a polarizing plate with a retardation layer is used for the purpose of improving display characteristics and preventing reflection. The polarizing plate with a retardation layer can usually be laminated on an image display panel via an adhesive layer. A substrate, wiring, etc. are arranged on the surface of the image display panel. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent Publication No. 2022-14611 Summary of the Invention [Problem to be solved by the invention]
[0004] When a polarizing plate with a retardation layer is attached to an image display panel, dents may occur on the viewing side of the polarizing plate with a retardation layer (i.e., the side not in contact with the image display device). The retardation layer, which is an oriented and solidified layer of a liquid crystal compound, is thinner than a retardation layer made of a resin film, so dents tend to occur more easily. Furthermore, in a polarizing plate with a retardation layer in which the retardation layer is sandwiched between pressure-sensitive adhesive layers, the occurrence of dents may be more noticeable. [Means for solving the problem]
[0005] 1. A polarizing plate with a retardation layer according to an embodiment of the present invention comprises, in this order, a polarizing plate including a polarizer; a first pressure-sensitive adhesive layer; a retardation layer which is an alignment solidified layer of a liquid crystal compound; and a second pressure-sensitive adhesive layer, and a resin film is laminated on the retardation layer via an adhesive layer. 2. In the retardation layer-attached polarizing plate of the above 1, the resin film may be laminated on the second pressure-sensitive adhesive layer side of the retardation layer. 3. In the retardation layer-attached polarizing plate according to 1 above, the resin film may be laminated on the first pressure-sensitive adhesive layer side of the retardation layer. 4. In the retardation layer-attached polarizing plate according to any one of the above 1 to 3, the resin film may be a cyclic olefin resin film. 5. In the retardation layer-attached polarizing plate according to any one of the above 1 to 4, the resin film may have a refractive index distribution of nx=ny>nz. 6. In the polarizing plate with a retardation layer according to any one of 1 to 5 above, the retardation layer may have Re(550) of 100 nm to 190 nm, Re(450) / Re(550) of <1, and the angle between the slow axis of the retardation layer and the absorption axis of the polarizer may be 40° to 50°. 7. The retardation layer-attached polarizing plate according to any one of the above items 1 to 6 may further include a retardation layer having a refractive index distribution of nz>nx=ny. 8. In another aspect of the present invention, there is provided an image display device, which comprises the retardation layer-attached polarizing plate according to any one of 1 to 7 above. 9. The image display device according to the above item 8 may be an organic electroluminescence display device. Effect of the Invention
[0006] According to the embodiment of the present invention, it is possible to provide a retardation layer-attached polarizing plate in which the occurrence of dents is suppressed. [Brief description of the drawings]
[0007] [Figure 1] 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to another embodiment of the present invention. [Diagram 3] FIG. 11 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to still another embodiment of the present invention. [Figure 4] FIG. 11 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to still another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0009] (Definition of terms and symbols) The definitions of terms and symbols used in this specification are as follows. (1) Refractive index (nx, ny, nz) "nx" is the refractive index in the direction in which the in-plane refractive index is maximum (i.e., the slow axis direction), "ny" is the refractive index in the direction perpendicular to the slow axis in the plane (i.e., the fast axis direction), and "nz" is the refractive index in the thickness direction. (2) In-plane phase difference (Re) "Re(λ)" is the in-plane retardation measured with light of wavelength λ nm at 23° C. For example, "Re(550)" is the in-plane retardation measured with light of wavelength 550 nm at 23° C. Re(λ) is calculated by the formula: Re(λ)=(nx-ny)×d, where d(nm) is the thickness of the layer (film). (3) Retardation in the thickness direction (Rth) "Rth(λ)" is the retardation in the thickness direction measured with light of wavelength λ nm at 23° C. For example, "Rth(550)" is the retardation in the thickness direction measured with light of wavelength 550 nm at 23° C. Rth(λ) is calculated by the formula: Rth(λ)=(nx-nz)×d, where d(nm) is the thickness of the layer (film). (4) Nz coefficient The Nz coefficient is calculated by Nz=Rth / Re. (5)Angle When angles are referred to herein, the angles include both clockwise and counterclockwise angles relative to a reference direction, so for example, "45°" means ±45°.
[0010] A. Overall structure of the polarizing plate with a retardation layer FIG. 1 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to one embodiment of the present invention. The retardation layer-attached polarizing plate of the illustrated example has a polarizing plate 10 including a polarizer 11; a first adhesive layer 20; a retardation layer 30; an adhesive layer 40; a resin film 50; and a second adhesive layer 60 in this order. The retardation layer 30 has a resin film 50 laminated thereon via an adhesive layer 40. In the illustrated example, the resin film 50 is laminated on the second adhesive layer 60 side of the retardation layer 30 via the adhesive layer 40, but the resin film 50 may be laminated on the first adhesive layer 20 side of the retardation layer 30 via the adhesive layer 40. The polarizing plate 10 typically includes a polarizer 11 and protective layers 12 and 13 arranged on both sides of the polarizer 11. The protective layer 13 may be omitted. For example, when the retardation layer can also function as a protective layer, the protective layer 13 may be omitted. The retardation layer 30 is a layer in which the liquid crystal compound is aligned and solidified (hereinafter, also referred to as a liquid crystal alignment solidified layer). The retardation layer 30 may be one layer, or may include two or more layers. When two or more retardation layers are included, at least one of the retardation layers may be a liquid crystal alignment solidified layer. In this embodiment, a resin film may be laminated on the retardation layer, which is a liquid crystal alignment solidified layer, via an adhesive layer. FIG. 2 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to another embodiment of the present invention. The retardation layer-attached polarizing plate of this illustrated example has a polarizing plate 10, a first adhesive layer 20, a first retardation layer 31, an adhesive layer 41, a second retardation layer 32, an adhesive layer 42, a resin film 50, and a second adhesive layer 60, in this order. In the illustrated example, the second retardation layer 32 is a liquid crystal alignment solidified layer. In the illustrated example, the resin film 50 is laminated on the second adhesive layer 60 side of the second retardation layer 32 via an adhesive layer 42. FIG. 3 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to yet another embodiment of the present invention. In the illustrated example, the first retardation layer 31 is a liquid crystal alignment solidified layer. In the illustrated example, the resin film 50 is laminated on the first adhesive layer side of the first retardation layer 31 via an adhesive layer 41. FIG. 4 is a schematic cross-sectional view of a retardation layer-attached polarizing plate according to yet another embodiment of the present invention. In the illustrated example, both the first retardation layer 31 and the second retardation layer 32 are liquid crystal alignment solidified layers.In the illustrated example, the resin film 50 is laminated on the second adhesive layer 60 side of the first retardation layer 31 via an adhesive layer 41. In addition, the resin film 50 is laminated on the first adhesive layer 20 side of the second retardation layer 32 via an adhesive layer 42. When the resin film is laminated to a component other than the retardation layer, it may be laminated via an adhesive layer or may be laminated via an adhesive layer. As described above, when two or more retardation layers that are liquid crystal alignment solidified layers are included, it is sufficient that a resin film is laminated on at least one retardation layer via an adhesive layer. In the illustrated example, there is one resin film, but two or more resin films may be included. In a retardation layer-attached polarizing plate including a retardation layer that is a liquid crystal alignment solidified layer, the occurrence of dents when laminating to an image display panel may be a problem. In addition, the occurrence of dents may be more noticeable in a retardation layer-attached polarizing plate in which the retardation layer is sandwiched between adhesive layers. A substrate, wiring, etc. are arranged on the surface of the image display panel on the side on which the retardation layer-attached polarizing plate is laminated, and the surface may have irregularities. The unevenness may be one of the causes of dents in the retardation layer-attached polarizing plate. In the retardation layer-attached polarizing plate according to the embodiment of the present invention, a resin film is laminated on the retardation layer, which is a liquid crystal alignment solidified layer, via an adhesive layer. With such a retardation layer-attached polarizing plate, it is possible to suppress the occurrence of dents when the plate is attached to an image display panel.
[0011] As described above, the retardation layer-attached polarizing plate 100 may have the second adhesive layer 60 as the outermost layer. The retardation layer-attached polarizing plate 100 can be attached to an image display device (substantially, an image display panel) via the second adhesive layer 60. For practical purposes, it is preferable that a release liner is temporarily attached to the surface of the second adhesive layer 60 until the retardation layer-attached polarizing plate is used. By temporarily attaching the release liner, the adhesive layer is protected until actual use, and the retardation layer-attached polarizing plate can be rolled.
[0012] The thickness of the retardation layer-attached polarizing plate may be set to any appropriate value. In one embodiment, the total thickness of the retardation layer-attached polarizing plate is preferably 150 μm or less, more preferably 140 μm or less, even more preferably 120 μm or less, more preferably 100 μm or less, even more preferably 90 μm or less, and particularly preferably 85 μm or less. The total thickness of the retardation layer-attached polarizing plate may be, for example, 30 μm or more. The total thickness of the retardation layer-attached polarizing plate refers to the sum of the thicknesses of the polarizing plate, the first adhesive layer, the retardation layer, the adhesive layer, the resin film, and the second adhesive layer (that is, the total thickness of the retardation layer-attached polarizing plate does not include the thickness of a release liner that may be temporarily attached to the surface of the second adhesive layer).
[0013] The components of the retardation layer-attached polarizing plate will be described in more detail below.
[0014] B. Polarizing plate B-1.Polarizer A polarizer is typically composed of a resin film containing a dichroic material (typically, iodine). As the resin film, any appropriate resin film that can be used as a polarizer can be adopted. The resin film is typically a polyvinyl alcohol resin (hereinafter, referred to as "PVA resin") film. The resin film may be a single-layer resin film or a laminate of two or more layers.
[0015] A specific example of a polarizer composed of a single-layer resin film is a PVA-based resin film that has been subjected to a dyeing treatment with iodine and a stretching treatment (typically, uniaxial stretching). The dyeing with iodine is performed, for example, by immersing the PVA-based resin film in an aqueous iodine solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching may be performed after the dyeing treatment or while dyeing. Alternatively, the film may be dyed after stretching. If necessary, the PVA-based resin film is subjected to a swelling treatment, a crosslinking treatment, a washing treatment, a drying treatment, or the like. For example, by immersing the PVA-based resin film in water and washing it before dyeing, not only can dirt and antiblocking agents on the surface of the PVA-based resin film be washed off, but also uneven dyeing can be prevented by swelling the PVA-based resin film.
[0016] Specific examples of polarizers obtained using a laminate include a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. A polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be produced by, for example, applying a PVA-based resin solution to the resin substrate and drying the resin substrate to form a PVA-based resin layer on the resin substrate to obtain a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is preferably formed on one side of the resin substrate. The stretching typically includes immersing the laminate in an aqueous boric acid solution to stretch it. Furthermore, the stretching may further include, as necessary, stretching the laminate in air at a high temperature (for example, 95° C. or higher) before stretching in the aqueous boric acid solution. In addition, in this embodiment, the laminate is preferably subjected to a drying shrinkage treatment in which the laminate is heated while being transported in the longitudinal direction to shrink the laminate by 2% or more in the width direction. Typically, the manufacturing method of this embodiment includes subjecting the laminate to an air-assisted stretching treatment, a dyeing treatment, an underwater stretching treatment, and a drying shrinkage treatment in this order. By introducing the auxiliary stretching, even when PVA is applied onto a thermoplastic resin, it is possible to increase the crystallinity of the PVA, and to achieve high optical properties. At the same time, by increasing the orientation of the PVA in advance, problems such as a decrease in the orientation or dissolution of the PVA when immersed in water in the subsequent dyeing and stretching steps can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in the orientation of the polyvinyl alcohol molecules can be suppressed compared to when the PVA-based resin layer does not contain a halide. This can improve the optical properties of a polarizer obtained through a treatment process in which the laminate is immersed in a liquid, such as a dyeing treatment and an underwater stretching treatment. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction by the drying shrinkage treatment.The obtained laminate of resin substrate / polarizer may be used as it is (i.e., the resin substrate may be used as a protective layer for the polarizer), or the resin substrate may be peeled off from the laminate of resin substrate / polarizer, and any suitable protective layer may be laminated on the peeled surface depending on the purpose. Details of the method for producing such a polarizer are described in, for example, JP-A-2012-73580 (Patent No. 5414738) and Japanese Patent No. 6470455. The entire disclosures of these publications are incorporated herein by reference.
[0017] The thickness of the polarizer is preferably 1 μm to 30 μm, more preferably 1 μm to 25 μm, further preferably 1 μm to 15 μm, further more preferably 1 μm to 10 μm, and particularly preferably 1 μm to 8 μm. When the thickness of the polarizer is within the above range, the retardation layer-attached polarizing plate can be made thinner.
[0018] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance Ts of the polarizer is preferably 40% to 48%, more preferably 41% to 46%. The degree of polarization P of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and even more preferably 99.9% or more. The single transmittance is typically a Y value measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. The degree of polarization is typically calculated by the following formula based on the parallel transmittance Tp and crossed transmittance Tc measured using an ultraviolet-visible spectrophotometer and subjected to luminosity correction. Degree of polarization (%)={(Tp-Tc) / (Tp+Tc)} 1 / 2 ×100
[0019] B-2.Protective layer The protective layers 12 and 13 are formed of any suitable film that can be used as a protective layer for a polarizer. Specific examples of materials that are the main components of the films include cellulose-based resins such as triacetyl cellulose (TAC), and transparent resins such as polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyethersulfones, polysulfones, polystyrenes, polynorbornenes, polyolefins, (meth)acrylics, and acetates. Other examples include thermosetting resins or ultraviolet-curing resins such as (meth)acrylics, urethanes, (meth)acrylic urethanes, epoxys, and silicones. Other examples include glassy polymers such as siloxane polymers. Polymer films described in JP 2001-343529 A (WO01 / 37007) can also be used. The material for this film may be, for example, a resin composition containing a thermoplastic resin having a substituted or unsubstituted imide group in the side chain, and a thermoplastic resin having a substituted or unsubstituted phenyl group and a nitrile group in the side chain, such as a resin composition containing an alternating copolymer of isobutene and N-methylmaleimide, and an acrylonitrile-styrene copolymer. The polymer film may be, for example, an extrusion molded product of the above resin composition.
[0020] The polarizing plate with a retardation layer is typically placed on the viewing side of an image display device, and the protective layer 12 is typically placed on the viewing side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coat treatment, anti-reflection treatment, anti-sticking treatment, and anti-glare treatment, as necessary.
[0021] The thickness of the protective layer is preferably 10 μm to 50 μm, and more preferably 10 μm to 30 μm. When a surface treatment is applied, the thickness of the outer protective layer (protective layer 12) includes the thickness of the surface treatment layer.
[0022] C. Retardation layer The retardation layer includes a retardation layer that is a liquid crystal alignment solidified layer. As described above, when the retardation layer is a liquid crystal alignment solidified layer, dents may become more noticeable when the retardation layer is attached to an image display panel. In an embodiment of the present invention, a resin film is laminated on the retardation layer that is a liquid crystal alignment solidified layer via an adhesive layer. If the retardation layer-attached polarizing plate is a plate in which a resin film is laminated via an adhesive layer, the occurrence of dents when the retardation layer-attached polarizing plate is attached to an image display panel can be suppressed. The retardation layer may be only one layer, or may include two or more layers. When two or more retardation layers are included, at least one retardation layer may be a liquid crystal alignment solidified layer, and all of the retardation layers included in the retardation layer-attached polarizing plate may be liquid crystal alignment solidified layers.
[0023] In one embodiment, the retardation layer may function as a λ / 4 plate. The retardation layer may be a single layer or a laminate of two or more layers. The retardation layer may further include an alignment layer and / or a substrate.
[0024] In one embodiment, the retardation layer is a single layer. The first retardation layer preferably has Re(550) of 100 nm to 190 nm, Re(450) / Re(550) of the retardation layer is <1, and the angle between the slow axis of the first retardation layer and the absorption axis of the polarizer is 40° to 50°. The in-plane retardation Re(550) of the retardation layer is preferably 100 nm to 190 nm, more preferably 110 nm to 170 nm, and further preferably 130 nm to 160 nm.
[0025] In this embodiment, the Nz coefficient of the retardation layer is preferably 0.9 to 1.5, and more preferably 0.9 to 1.3. If such a relationship is satisfied, when the obtained retardation layer-attached polarizing plate is used in an image display device, an extremely excellent reflection hue can be achieved.
[0026] The thickness of the retardation layer is preferably 10 μm or less, more preferably 0.5 μm to 10 μm, further preferably 0.5 μm to 7 μm, and particularly preferably 1 μm to 5 μm.
[0027] The retardation layer preferably exhibits inverse dispersion wavelength characteristics. In this case, Re(550) / Re(650) is preferably greater than 1, more preferably greater than 1 and less than 1.2, and even more preferably 1.01 to 1.15. The retardation layer preferably has Re(450) / Re(550) less than 1, more preferably 0.8 or more and less than 1, and even more preferably 0.8 or more and 0.95 or less. With this configuration, it is possible to realize very excellent antireflection characteristics.
[0028] In this embodiment, the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and even more preferably about 45°. If the angle is in this range, by using a λ / 4 plate as the retardation layer, a polarizing plate with a retardation layer having very excellent circular polarization properties (as a result, very excellent antireflection properties) can be obtained.
[0029] As described above, the retardation layer is an alignment solidified layer of a liquid crystal compound. By using a liquid crystal compound, the difference between nx and ny of the obtained retardation layer can be significantly increased compared to non-liquid crystal materials, so the thickness of the retardation layer to obtain a desired in-plane retardation can be significantly reduced. As a result, the retardation layer-attached polarizing plate can be further thinned.
[0030] The retardation layer, which is an alignment solidification layer of a liquid crystal compound, can be formed using a composition containing a polymerizable liquid crystal compound. In this specification, the polymerizable liquid crystal compound contained in the composition refers to a compound having a polymerizable group and having liquid crystal properties. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group refers to a group that can be involved in a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator.
[0031] The liquid crystal property may be expressed by thermotropic or lyotropic. The liquid crystal phase may be nematic or smectic. From the viewpoint of ease of manufacture, the liquid crystal property is preferably a thermotropic nematic liquid crystal. Details of the retardation layer, which is such a liquid crystal alignment solidification layer, are described, for example, in JP-A-2023-75790. This publication is incorporated herein by reference in its entirety.
[0032] In one embodiment, the retardation layer-attached polarizing plate may further include another retardation layer (also referred to as a second retardation layer). The other retardation layer may be a stretched film of a polymer film or a liquid crystal alignment solidified layer. The other retardation layer may be a so-called positive C plate whose refractive index characteristics show the relationship of nz>nx=ny. If a positive C plate is used as the other retardation layer, reflection in an oblique direction can be effectively prevented, and the anti-reflection function can be made to have a wide viewing angle. According to the embodiment of the present invention, even if a liquid crystal alignment solidified layer is used as the other retardation layer, the occurrence of dents during bonding to an image display panel can be suppressed. The thickness direction retardation Rth(550) of the other retardation layer, which is a liquid crystal alignment solidified layer, is preferably -50 nm to -300 nm, more preferably -70 nm to -250 nm, further preferably -90 nm to -200 nm, and particularly preferably -100 nm to -180 nm. Here, "nx=ny" includes not only the case where nx and ny are strictly equal, but also the case where nx and ny are substantially equal. That is, the in-plane retardation Re(550) of the other retardation layer, which is a liquid crystal alignment solidified layer, can be less than 10 nm.
[0033] The liquid crystal alignment solidified layer having a refractive index characteristic of nz>nx=ny may be formed of any appropriate material. It is preferably made of a film containing a liquid crystal material fixed in homeotropic alignment. The liquid crystal material (liquid crystal compound) that can be homeotropically aligned may be a liquid crystal monomer or a liquid crystal polymer. Specific examples of the liquid crystal compound and the method of forming the retardation layer include the liquid crystal compound and the method of forming the retardation layer described in
[0020] to
[0028] of JP-A-2002-333642. In this case, the thickness of the separate retardation layer is preferably 0.5 μm to 10 μm, more preferably 0.5 μm to 8 μm, and even more preferably 0.5 μm to 5 μm.
[0034] D. Resin film Any suitable resin film can be used as the resin film. As described above, if the resin film is laminated on the retardation layer, which is the liquid crystal alignment solidification layer, via an adhesive layer, the occurrence of dents during lamination to the image display panel can be suppressed. Any suitable resin can be used as the resin constituting the resin film. For example, cyclic olefin resins such as norbornene resins, acrylic resins, polycarbonate resins, cellulose resins, etc. are listed. Norbornene resins are preferable. Only one type of resin may be used, or two or more types may be used in combination. In addition, the resin film may be a single film, or may be a laminate of two or more. It is preferable that the resin film is not stretched (unstretched resin film).
[0035] The thickness of the resin film can be set to any appropriate value. The thickness of the resin film is preferably 1 μm to 40 μm, more preferably 3 μm to 30 μm, and further preferably 5 μm to 20 μm. If the thickness of the resin film is within the above range, the occurrence of dents during attachment to an image display panel can be suppressed.
[0036] The resin film may have any suitable refractive index distribution. In one embodiment, the resin film may be a so-called negative C plate, which preferably satisfies the refractive index distribution of nx=ny>nz. If the resin film is a negative C plate, a retardation layer-attached polarizing plate having excellent image display characteristics can be provided.
[0037] The smaller the in-plane retardation Re(550) of the resin film, the more preferable. The in-plane retardation Re(550) of the resin film is preferably 20 nm or less, more preferably 15 nm or less, even more preferably 10 nm or less, and particularly preferably 5 nm or less. If the in-plane retardation Re(550) of the resin film is within the above range, a retardation layer-attached polarizing plate having excellent image display characteristics can be provided. The in-plane retardation Re(550) is, for example, 0 nm or more.
[0038] The smaller the absolute value of the retardation Rth(550) in the thickness direction of the resin film, the more preferable. The absolute value of the retardation Rth(550) in the thickness direction of the resin film is preferably 20 nm or less, more preferably 15 nm or less, even more preferably 10 nm or less, and particularly preferably 5 nm or less. If the absolute value of the retardation Rth(550) in the thickness direction of the resin film is within the above range, a retardation layer-attached polarizing plate having excellent image display characteristics can be provided. The absolute value of the retardation Rth(550) in the thickness direction is, for example, 0 nm or more.
[0039] The total light transmittance of the resin film is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The total light transmittance of the resin film is, for example, 99% or less. If the total light transmittance of the resin film is within the above range, a retardation layer-attached polarizing plate having excellent image display properties can be provided. The total light transmittance of the resin film can be measured in accordance with JIS K 7361.
[0040] The haze of the resin film is preferably 10% or less, more preferably 5% or less, even more preferably 1% or less, and particularly preferably 0.5% or less. For example, the haze is 0.1% or more. If the haze of the resin film is within the above range, a retardation layer-attached polarizing plate having excellent image display properties can be provided. The haze of the resin film can be measured according to JIS K 7361.
[0041] The tensile modulus of the resin film is preferably 1000 MPa to 3000 MPa, more preferably 1200 MPa to 2500 MPa, and further preferably 1500 MPa to 2000 MPa. If the tensile modulus of the resin film is within the above range, the occurrence of dents during bonding to an image display panel can be suppressed. The tensile modulus of the resin film can be measured at room temperature (23°C) in accordance with JIS K 7161.
[0042] The tensile breaking strength of the resin film is preferably 0.5 N to 20 N, more preferably 1 N to 15 N, and further preferably 3 N to 12 N. When the tensile modulus of the resin film is within the above range, the occurrence of dents during bonding to an image display panel can be suppressed. The tensile breaking strength of the resin film can be measured at room temperature (23°C) in accordance with JIS K 7161.
[0043] The breaking elongation of the resin film is preferably 1% to 10%, more preferably 2% to 8%, and further preferably 3% to 7%. If the breaking elongation of the resin film is within the above range, the occurrence of dents during bonding to an image display panel can be suppressed. The breaking elongation of the resin film can be measured by using a thermomechanical analyzer (TMA).
[0044] The moisture permeability of the resin film is preferably 20 g / m 2 / 24 hours~60g / m 2 / 24 hours, more preferably 25 g / m 2 / 24 hours~50g / m 2 / 24 hours, more preferably 30 g / m 2 / 24 hours~40g / m2 / 24 hours. If the moisture permeability of the resin film is within the above range, the occurrence of dents during bonding to an image display panel can be suppressed. The moisture permeability of the resin film can be measured in accordance with JIS Z 0208 under conditions of a temperature of 40°C and a humidity of 92% RH.
[0045] E. Adhesive layer The first adhesive layer and the second adhesive layer may be formed of any suitable adhesive. Specific examples of adhesives constituting the adhesive layer include acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, epoxy adhesives, and polyether adhesives. By adjusting the type, number, combination, and compounding ratio of monomers forming the base resin of the adhesive, as well as the compounding amount of the crosslinking agent, reaction temperature, reaction time, etc., an adhesive having desired properties according to the purpose can be prepared. The base resin of the adhesive may be used alone or in combination of two or more types. The first adhesive layer and the second adhesive layer may be formed of the same adhesive or different adhesives. From the viewpoints of transparency, processability, durability, etc., an acrylic adhesive (acrylic adhesive composition) is preferred.
[0046] The acrylic pressure-sensitive adhesive typically contains a (meth)acrylic polymer as a main component, and the (meth)acrylic polymer may be contained in the pressure-sensitive adhesive in an amount of, for example, 50% by weight or more, preferably 70% by weight or more, and more preferably 90% by weight or more of the solid content of the pressure-sensitive adhesive.
[0047] The (meth)acrylic polymer contains alkyl (meth)acrylate as a main component as a monomer unit. Here, (meth)acrylate refers to acrylate and / or methacrylate. The alkyl (meth)acrylate may be contained in a proportion of preferably 80% by weight or more, more preferably 90% by weight or more, in the monomer components forming the (meth)acrylic polymer. Examples of the alkyl group of the alkyl (meth)acrylate include linear or branched alkyl groups having 1 to 18 carbon atoms. The average carbon number of the alkyl group is preferably 3 to 9, more preferably 3 to 6.
[0048] The acrylic adhesive may preferably contain a silane coupling agent and / or a crosslinking agent. Examples of the silane coupling agent include an epoxy group-containing silane coupling agent. Examples of the crosslinking agent include an isocyanate-based crosslinking agent and a peroxide-based crosslinking agent. Furthermore, the acrylic adhesive composition may contain an antioxidant and / or a conductive agent. Details of the adhesive layer or the acrylic adhesive composition are described in, for example, JP 2006-183022 A, JP 2015-199942 A, JP 2018-053114 A, JP 2016-190996 A, and WO 2018 / 008712 A, and the descriptions in these publications are incorporated herein by reference.
[0049] The thickness of the pressure-sensitive adhesive layer may be set to any appropriate value. The thickness of the first pressure-sensitive adhesive layer is preferably 2 μm to 50 μm, more preferably 3 μm to 30 μm, and even more preferably 5 μm to 15 μm. The thickness of the second pressure-sensitive adhesive layer is preferably 10 μm to 100 μm, more preferably 15 μm to 70 μm, and even more preferably 20 μm to 50 μm. When the thickness of the pressure-sensitive adhesive layer is within the above range, the adhesion between the respective constituent members can be sufficiently ensured.
[0050] F.Adhesive layer The adhesive layer may be formed of any suitable adhesive. For example, an active energy ray curable adhesive may be used. As the active energy ray curable adhesive, any suitable active energy ray curable adhesive may be used, for example, an ultraviolet ray curable adhesive or an electron beam curable adhesive.
[0051] The active energy ray curable adhesive typically contains a monofunctional component, a polyfunctional component (curing component), and a photopolymerization initiator. The monofunctional component and the polyfunctional component are typically radical polymerizable compounds. Preferred monofunctional components include, for example, higher alkyl esters of (meth)acrylic acid and modified products thereof. Specific examples include isostearyl acrylate, lauryl acrylate, acryloylmorpholine, unsaturated fatty acid hydroxyalkyl ester modified ε-caprolactone, and the like. Preferred polyfunctional components include, for example, monomers and / or oligomers having two or more functional groups such as (meth)acrylate groups and (meth)acrylamide groups. Specific examples include polyethylene glycol diacrylate, trimethylpropane triacrylate, and glycerin triacrylate. Specific examples of monofunctional or polyfunctional components other than those mentioned above include tripropylene glycol diacrylate, 1,9-nonanediol diacrylate, tricyclodecane dimethanol diacrylate, phenoxydiethylene glycol acrylate, cyclic trimethylolpropane formal acrylate, dioxane glycol diacrylate, EO-modified diglycerin tetraacrylate, γ-butyrolactone acrylate, N-methylpyrrolidone, hydroxyethyl acrylamide, N-methylol acrylamide, N-methoxymethyl acrylamide, N-ethoxymethyl acrylamide, and 9-vinyl carbazole. In one embodiment, the monofunctional or polyfunctional component has a ring structure. Specific examples include acryloylmorpholine, γ-butyrolactone acrylate, unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone, N-methylpyrrolidone, and 9-vinyl carbazole. The monofunctional or polyfunctional components may each be used alone or in combination of two or more.
[0052] The active energy ray curable adhesive may further contain a cationic polymerizable compound as required. The cationic polymerizable compound may be monofunctional or polyfunctional. Examples of the monofunctional cationic polymerizable compound include p-tert-butylphenyl glycidyl ether and 3-ethyl-3-[(2-ethylhexyl)oxy]oxetane. Examples of the polyfunctional cationic polymerizable compound include 3-ethyl-3-{[(3-ethyloxetane-3-yl)methoxy]methyl}oxetane. A silane coupling agent may be used as the cationic polymerizable compound. Examples of the silane coupling agent include 3-glycidoxypropyltrimethoxysilane.
[0053] The active energy ray curable adhesive may further contain any suitable additive. For example, a plasticizer (e.g., an oligomer component), a crosslinking agent, a diluent, etc. These additives are used in any suitable content depending on the purpose.
[0054] Details of the active energy ray-curable adhesive are described, for example, in JP 2018-017996 A. The disclosure of this publication is incorporated herein by reference.
[0055] The thickness of the adhesive layer is preferably 0.3 μm to 3 μm, more preferably 0.6 μm to 2 μm, and further preferably 0.9 μm to 1.5 μm. When the thickness of the adhesive layer is within the above range, the retardation layer and the resin film can be appropriately adhered to each other.
[0056] G. Image display device The retardation layer-attached polarizing plate described in the above items A to F can be applied to an image display device. Therefore, the embodiment of the present invention includes an image display device using such a retardation layer-attached polarizing plate. Representative examples of image display devices include liquid crystal display devices and electroluminescence (EL) display devices (e.g., organic EL display devices and inorganic EL display devices). The image display device according to the embodiment of the present invention can include the retardation layer-attached polarizing plate on the viewing side. The retardation layer-attached polarizing plate can be laminated so that the retardation layer is on the image display cell (e.g., liquid crystal cell, organic EL cell, inorganic EL cell) side (so that the polarizer is on the viewing side). As described above, the retardation layer-attached polarizing plate of the embodiment of the present invention can suppress the occurrence of dents when it is attached to an image display panel. Therefore, the productivity of the image display device can be improved. EXAMPLES
[0057] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The methods for measuring each property are as follows. In the examples and comparative examples, "parts" and "%" are by weight unless otherwise specified.
[0058] (1) Thickness The thickness of 10 μm or less was measured using an interference film thickness meter (manufactured by Otsuka Electronics, product name "MCPD-3000"), and the thickness of more than 10 μm was measured using a digital micrometer (manufactured by Anritsu, product name "KC-351C").
[0059] (2) Load-bearing compression evaluation The polarizing plates with retardation layers obtained in the examples and comparative examples were cut into a length of 1 cm and a width of 1 cm to prepare samples. The second adhesive layer of the sample was attached to an aluminum sheet (aluminum reflector (manufactured by Toray Film Processing Co., Ltd., product name "Cerapeel DMS-X42", total light reflectance: 86%)). Then, the sample was placed on a glass plate (manufactured by Matsunami Glass Industry Co., Ltd., thickness: 0.7 mm) so that the surface of the hard coat layer of the sample was in contact with the glass plate. Then, a weight was placed on a cone-shaped indenter (diameter 1.5 mm) from the aluminum sheet side via a polyethylene terephthalate (PET) sheet (manufactured by Toray Industries, Inc., thickness 80 μm) and pressed for 10 seconds. The weight (load) of the weight was changed to 300 g (1.7 MPa), 400 g (2.2 MPa), and 500 g (2.8 MPa), and measurements were performed. After that, the weight and the indenter were removed, and the surface of the retardation layer-attached polarizing plate that had been in contact with the glass plate was visually observed in reflection at a polar angle of 30° to 60° and around one azimuth angle to confirm the presence or absence of dents, and the maximum load at which no dents were observed was defined as the load capacity. In addition, when the surface of the retardation layer-attached polarizing plate is defined as the X-axis and the Y-axis, and the axis perpendicular to the XY plane is defined as the Z-axis, the angle inclined from the Z-axis to the XY plane direction was defined as the polar angle (θ), and the MD direction of the polarizing plate used in the retardation layer-attached polarizing plate was defined as 0°, and the measurement angle defined between the MD direction of this polarizing plate and the counterclockwise direction was defined as the azimuth angle (φ) for evaluation.
[0060] (3) Reflective hue (polar angle 45° hue) The polarizing plates with retardation layers obtained in the examples and comparative examples were cut into a length of 1 cm and a width of 1 cm to prepare samples. The second adhesive layer of the sample was attached to an aluminum reflector (manufactured by Toray Film Processing Co., Ltd., product name "Cerapeel DMS-X42", total light reflectance: 86%). When observing the sample in reflection at a polar angle of 45° around one azimuth angle, the sample with a change in color was rated as 1, and the sample without a change in color was rated as 2. Observation was also performed at a polar angle of 0°, and the sample with a color that matched the color around one azimuth angle was rated as 3 for evaluation.
[0061] (4) Judgment The suitability of the retardation layer-attached polarizing plate for use in an image display device was evaluated according to the following criteria. 〇〇 (best): Load resistance exceeds 2MPa in the indentation test, and the reflection hue is 3. ○ (Good): The load resistance test exceeds 2 MPa and the reflection hue is 2. △ (Acceptable): The load resistance test exceeds 2 MPa and the reflection hue is 1. × (Not acceptable): Load resistance does not exceed 2MPa in the indentation test
[0062] [Production Example 1] Preparation of adhesive composition 1. Preparation of Base Polymer A monomer mixture containing 94.9 parts by weight of butyl acrylate (BA), 5 parts by weight of acrylic acid (AA), and 0.1 parts by weight of 2-hydroxyethyl acrylate (HEA) was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Next, 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with ethyl acetate for 100 parts by weight of the monomer mixture (solid content), and nitrogen gas was introduced while gently stirring to replace the nitrogen. The liquid temperature in the flask was kept at around 55°C and a polymerization reaction was carried out for 7 hours. Then, ethyl acetate was added to the resulting reaction solution to obtain a solution of a (meth)acrylic polymer with a weight average molecular weight of 2 million, adjusted to a solid content concentration of 30%.
[0063] 2. Preparation of acrylic adhesive composition An acrylic adhesive composition was prepared by blending 0.6 parts by weight of an isocyanate crosslinking agent (trimethylolpropane / tolylene diisocyanate adduct, manufactured by Tosoh Corporation, product name "Coronate L") and 0.1 parts by weight of a silane coupling agent (product name: KBM403, manufactured by Shin-Etsu Chemical Co., Ltd.) with 100 parts by weight of the solid content of the obtained (meth)acrylic polymer solution.
[0064] [Production Example 2] Preparation of UV-curable adhesive A UV-curable adhesive A was prepared by mixing 50 parts by weight of unsaturated fatty acid hydroxyalkyl ester-modified ε-caprolactone (manufactured by Daicel Corporation, product name "Placcel FA-1DDM"), 10 parts by weight of polyethylene glycol diacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Acrylate 9EG-A"), 20 parts by weight of acryloyl morpholine, 15 parts by weight of acrylic polymer (manufactured by Toagosei Co., Ltd., product name "ARUFON UP-1190"), 3 parts by weight of photopolymerization initiator (manufactured by IGM Resins, product name "Omnirad 907"), and 2 parts by weight of photopolymerization initiator (manufactured by Nippon Kayaku Co., Ltd., product name "KAYACURE-DETX-S").
[0065] [Example 1] <Preparation of polarizing plate> 1. Preparation of Polarizer As a thermoplastic resin substrate, a long amorphous isophthalic copolymerized polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one side of the resin substrate was subjected to a corona treatment. A PVA aqueous solution (coating solution) was prepared by adding 13 parts by weight of potassium iodide to 100 parts by weight of a PVA-based resin made by mixing polyvinyl alcohol (polymerization degree 4200, saponification degree 99.2 mol%) and acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., product name "GOHSEFFIMER") in a ratio of 9:1, and dissolving the mixture in water. The above PVA aqueous solution was applied to the corona-treated surface of a resin substrate and dried at 60° C. to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate. The obtained laminate was uniaxially stretched 2.4 times in the machine direction (longitudinal direction) in an oven at 130° C. (auxiliary air stretching treatment). Next, the laminate was immersed in an insolubilizing bath (a boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilizing treatment). Next, the film was immersed in a dye bath (an aqueous iodine solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 with 100 parts by weight of water) at a liquid temperature of 30°C for 60 seconds while adjusting the concentration so that the single transmittance (Ts) of the finally obtained polarizer would be the desired value (dyeing treatment). Next, the piece was immersed in a crosslinking bath (a boric acid aqueous solution obtained by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment). Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration: 4% by weight, potassium iodide concentration: 5% by weight) at a liquid temperature of 70°C and uniaxially stretched in the longitudinal direction (longitudinal direction) between rolls with different peripheral speeds to a total stretch ratio of 5.5 times (underwater stretching treatment). Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution obtained by mixing 4 parts by weight of potassium iodide with 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment). Thereafter, the film was dried in an oven maintained at about 90° C. while being brought into contact with a SUS heated roll whose surface temperature was maintained at about 75° C. (drying shrinkage treatment). In this manner, a polarizer having a thickness of 6 μm was formed on the resin substrate, and a polarizing plate having a resin substrate / polarizer structure was obtained. The single transmittance Ts of the polarizer was 43.3%.
[0066] 2. Preparation of Polarizing Plates An HC-COP film was attached to the surface of the obtained polarizer (the surface opposite to the resin substrate) via an ultraviolet-curing adhesive. The HC-COP film was a film in which a hard coat (HC) layer (thickness 4 μm) was formed on a cycloolefin resin (COP) film (thickness 25 μm), and the COP film was attached to the polarizer side. The COP film had a Re (550) of 135 nm. Next, the resin substrate was peeled off, and a triacetyl cellulose (TAC) film (thickness 20 μm) was attached to the peeled surface via an ultraviolet-curing adhesive. In this way, a polarizing plate having a configuration of HC layer / COP film (protective layer) / polarizer / TAC film (protective layer) was obtained.
[0067] <Manufacture of Retardation Layer 1> 55 parts by weight of the compound represented by formula (I), 25 parts by weight of the compound represented by formula (II), and 20 parts by weight of the compound represented by formula (III) were added to 400 parts by weight of cyclopentanone (CPN), and then heated to 60°C and stirred to dissolve. Then, the solution of the above-mentioned compound was returned to room temperature, and 3 parts by weight of Irgacure 907 (manufactured by BASF Japan Ltd.), 0.2 parts by weight of Megafac F-554 (manufactured by DIC Corporation), and 0.1 parts by weight of p-methoxyphenol (MEHQ) were added to the solution of the above-mentioned compound, and further stirred. The solution after stirring was transparent and uniform. The obtained solution was filtered through a 0.20 μm membrane filter to obtain a polymerizable composition. Also, a polyimide solution for an alignment film was applied to a glass substrate having a thickness of 0.7 mm by spin coating, and a coating film was obtained by drying at 100° C. for 10 minutes and then baking at 200° C. for 60 minutes. The obtained coating film was subjected to a rubbing treatment using a commercially available rubbing device to form an alignment film. Next, the polymerizable composition obtained above was applied to the substrate (substantially the alignment film) by spin coating, and dried at 100° C. for 2 minutes. After the obtained coating film was cooled to room temperature, it was heated with a high-pressure mercury lamp at 30 mW / cm 2 The film was irradiated with ultraviolet light at an intensity of 100 nm for 30 seconds to obtain a retardation layer (thickness 1 μm) which is an alignment solidified layer of the liquid crystal compound. The in-plane retardation Re(550) of the retardation layer was 149 nm. The retardation layer also had a Re(450) / Re(550) of 0.851, which showed reverse dispersion wavelength characteristics. The retardation layer can function as a λ / 4 plate. [ka] [ka]
[0068] A 10 μm thick adhesive layer (first adhesive layer) was formed on the TAC film of the polarizing plate obtained above using the adhesive obtained in Production Example 1. Next, the retardation layer was attached to this adhesive layer. The lamination was performed so that the slow axis direction of the retardation layer forms an angle of 45° clockwise with respect to the absorption axis direction of the polarizer. Next, the adhesive obtained in Production Example 2 was applied to the retardation layer to a thickness of 1 μm, and a resin film (manufactured by Nippon Zeon Co., Ltd., product name "ZEONOR Film ZF14", thickness 13 μm) and the retardation layer were attached via the adhesive layer. The properties of the resin film are shown in Table 1. Next, a 25 μm thick adhesive layer (second adhesive layer) was formed on the resin film using the adhesive obtained in Production Example 1, and a retardation layer-attached polarizing plate was obtained. Note that, until evaluation, a 38 μm thick polyethylene terephthalate film (PET film, separator) treated with a silicone-based release agent was attached to the second adhesive layer. The results are shown in Table 2.
[0069] [Table 1]
[0070] [Example 2] <Preparation of Retardation Layer 2> A liquid crystal coating solution was prepared by dissolving 20 parts by weight of a side-chain liquid crystal polymer represented by the following chemical formula (the numbers 65 and 35 in the formula indicate the mole percent of the monomer unit, and are conveniently expressed as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure 907) in 200 parts by weight of cyclopentanone. The coating solution was then applied to a PET substrate that had been subjected to a vertical alignment treatment using a bar coater, and the liquid crystal was aligned by heating and drying at 80°C for 4 minutes. The liquid crystal layer was irradiated with ultraviolet light to harden the liquid crystal layer, thereby forming a retardation layer (thickness 1 μm) exhibiting a refractive index characteristic of nz>nx=ny on the substrate. [ka]
[0071] The adhesive obtained in Production Example 2 was applied to the retardation layer to a thickness of 1 μm, and the above-mentioned retardation layer 2 was laminated. Next, the substrate was peeled off from the retardation layer 2, and the adhesive obtained in Production Example 2 was applied to the surface from which the substrate was peeled off to a thickness of 1 μm, and a resin film (manufactured by Zeon Corporation, product name "ZEONOR FILM ZF14", thickness 13 μm) and the retardation layer 2 were laminated via an adhesive layer. Other than these, a polarizing plate with a retardation layer was obtained in the same manner as in Example 1. The results are shown in Table 2.
[0072] [Example 3] A resin film (manufactured by Zeon Corporation, trade name "ZEONORFILM ZF14", thickness 13 μm) was attached to the first adhesive layer. Separately, the adhesive obtained in Production Example 2 was applied to the retardation layer 1 and the retardation layer 2 to a thickness of 1 μm and attached to each other to produce a retardation layer laminate. The adhesive obtained in Production Example 2 was applied to the resin film attached to the polarizing plate to a thickness of 1 μm, and the first retardation layer side of the retardation layer laminate was attached to each other. Next, a 25 μm thick adhesive layer (second adhesive layer) was formed on the retardation layer 2 using the adhesive obtained in Production Example 1. A polarizing plate with a retardation layer was obtained in the same manner as in Example 1 except for these. The results are shown in Table 2.
[0073] [Example 4] In Example 2, the adhesive obtained in Production Example 2 was applied to the resin film attached to the retardation layer 1 to a thickness of 1 μm, and the retardation layer 2 produced in Example 2 was attached thereto, and a 25 μm-thick adhesive layer (second adhesive layer) was formed on the retardation layer 2 using the adhesive obtained in Production Example 1. A polarizing plate with a retardation layer was obtained in the same manner as in Example 1. The results are shown in Table 2.
[0074] Comparative Example 1 A polarizing plate with a retardation layer was obtained in the same manner as in Example 1, except that no resin film was attached to the retardation layer 1. The results are shown in Table 2.
[0075] Comparative Example 2 A polarizing plate with a retardation layer was obtained in the same manner as in Example 2, except that a second pressure-sensitive adhesive layer was formed without laminating a resin film to the retardation layer 2. The results are shown in Table 2.
[0076] Comparative Example 3 A polarizing plate with a retardation layer was obtained in the same manner as in Example 2, except that the resin film was laminated via a 5 μm-thick adhesive layer formed using the adhesive obtained in Production Example 1 instead of the adhesive. The results are shown in Table 2.
[0077] Comparative Example 4 A polarizing plate with a retardation layer was obtained in the same manner as in Example 3, except that the resin film was laminated via a 5 μm-thick adhesive layer formed using the adhesive obtained in Production Example 1 instead of the adhesive. The results are shown in Table 2.
[0078] [Table 2]
[0079] [evaluation] As is clear from Table 2, the retardation layer-attached polarizing plates of the examples of the present invention suppressed the occurrence of dents and were excellent in display characteristics. [Industrial Applicability]
[0080] The retardation layer-attached polarizing plate according to the embodiment of the present invention can be suitably used in image display devices such as liquid crystal display devices, organic EL display devices, and inorganic EL display devices. [Explanation of symbols]
[0081] 10 Polarizing plate 11 Polarizer 12 Protective layer 13 Protective layer 20 First adhesive layer 30 Retardation layer 31 First retardation layer 32 Second retardation layer 40 Adhesive layer 50 Resin Film 60 Second adhesive layer 100 Polarizing plate with retardation layer
Claims
1. The liquid crystal display device has, in this order, a polarizing plate including a polarizer; a first pressure-sensitive adhesive layer; a retardation layer which is an alignment and solidification layer of a liquid crystal compound; and a second pressure-sensitive adhesive layer, A polarizing plate with a retardation layer, in which a resin film is laminated on the retardation layer via an adhesive layer.
2. The polarizing plate with a retardation layer according to claim 1 , wherein the resin film is laminated on the second pressure-sensitive adhesive layer side of the retardation layer.
3. The polarizing plate with a retardation layer according to claim 1 , wherein the resin film is laminated on the first pressure-sensitive adhesive layer side of the retardation layer.
4. The retardation layer-attached polarizing plate according to claim 1 , wherein the resin film is a cyclic olefin-based resin film.
5. 2. The polarizing plate with a retardation layer according to claim 1, wherein the resin film has a refractive index distribution of nx=ny>nz.
6. The retardation layer has an Re(550) of 100 nm to 190 nm, Re(450) / Re(550) is <1, and the angle between the slow axis of the retardation layer and the absorption axis of the polarizer is 40° to 50°.
7. The polarizing plate with a retardation layer according to claim 1 , further comprising a retardation layer having a refractive index distribution of nz>nx=ny.
8. An image display device comprising the retardation layer-attached polarizing plate according to claim 1 .
9. 9. The image display device according to claim 8, which is an organic electroluminescence display device.
Citation Information
Patent Citations
Control device for vehicular headlight, control method for vehicular headlight, and vehicular headlight system
JP2022014611A